2016
DOI: 10.1186/s12884-016-0928-6
|View full text |Cite
|
Sign up to set email alerts
|

The status of maternal and newborn health care services in Zanzibar

Abstract: BackgroundIt is estimated that 287,000 women worldwide die annually from pregnancy and childbirth-related conditions, and 6.9 million under-five children die each year, of which about 3 million are newborns. Most of these deaths occur in sub-Saharan Africa. The maternal health situation in Tanzania mainland and Zanzibar is similar to other sub-Saharan countries. This study assessed the availability, accessibility and quality of emergency obstetric care services and essential resources available for maternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 15 publications
4
43
1
Order By: Relevance
“…Being an EmONC facility reassures the readiness of the facility to effectively manage women with direct obstetric complications that claim majority of maternal deaths. The current results are comparable or better than the results reported in other African countries including Ghana (7.7%), Zanzibar (7.6%), Nigeria, South Africa and Zambia [8,[11][12][13][14]. In contrast to most these studies, the 90% obstetric care facilities that could not provide the full set of EmONC functions renders a huge potential for promotion into EmONC facilities.…”
Section: Discussioncontrasting
confidence: 56%
“…Being an EmONC facility reassures the readiness of the facility to effectively manage women with direct obstetric complications that claim majority of maternal deaths. The current results are comparable or better than the results reported in other African countries including Ghana (7.7%), Zanzibar (7.6%), Nigeria, South Africa and Zambia [8,[11][12][13][14]. In contrast to most these studies, the 90% obstetric care facilities that could not provide the full set of EmONC functions renders a huge potential for promotion into EmONC facilities.…”
Section: Discussioncontrasting
confidence: 56%
“…The level of their pediatric care was relatively low as our previous study found [31][32][33] and make the score of fluid therapy had the biggest passing population in this study. Fakih and colleagues [6] pointed out that according to the minimum staffing requirements of Zanzibar, the human resources of the surveyed among 79 medical institutions were inadequate, qualified staffs including medical doctors, nurses and general surgeons were limited. These findings were consistent with our study.…”
Section: Pediatric Knowledge Of Doctors and Nurses Was Not Ideal In Zmentioning
confidence: 99%
“…Zanzibar belongs to Tanzania with a population of 1.3 million. Although the help babies breathy (HBB) training program and the Integrated Management of Childhood Illness (IMCI) Strategy for Children Under Five [4] has been performed across over hospitals of Tanzania [4][5] there is still high mortality rate of children in that country [5], The reason why this condition occurred in Zanzibar are due to its insufficient human resources and lack of medical facilities and equipment [6], thus leading to an urgent requirement for systematic and standardized appropriate pediatric care technology training of medical staffs, so as to improve children health and decrease mortality rate in children under 5 years old.…”
Section: Introductionmentioning
confidence: 99%
“…Facility-based data show an increase of maternal deaths from 187 per 100,000 live births in 2014 to 276 per 100,000 live births in 2016. Differently to another context, most of such deaths in Zanzibar occur within the health facilities owing to close proximity to health facilities for the 95% of the population (8). With such good access to health facilities, the main challenge was the quality of health services, particularly the emergency obstetric and neonatal care (EmONC) (9).…”
Section: Imentioning
confidence: 99%
“…Monitoring the progress made with response to investment in maternal and newborn health, helps to E gauge the effectiveness of the interventions. In Zanzibar, the ministry of health in collaboration with UNFPA conducted the first EmONC assessment in 2012 (8). Addressing the burden of maternal health needs continuous monitoring of signal functions for EmONC.…”
Section: Imentioning
confidence: 99%